Exploring the interaction of trade openness, income inequality, and poverty in Nigeria - Olukayode Emmanuel Maku; Jimoh Sina Ogede; Oluwaseyi Adedayo Adelowokan; Bamidele Olaitan Oshinowo (Journal of Enterprise and Development (JED), 2021)
The literature on the nexus between trade openness, income inequality and poverty appears conspicuously and of diverse outcomes. Perhaps, the mixed findings may be attributed to the methodology and economic structure of the country in view. The current study examines the trade openness on income inequality and poverty in Nigeria between 1981 and 2019 using Autoregressive Distributed Lags (ARDL) methodology. Our findings show that trade openness had different effects on inequality and poverty in Nigeria in the short and long run. While its relationship with inequality is a short-run phenomenon, it had a long-run relationship with poverty. Overall, trade openness had a declining effect on inequality and poverty. In the former, its impact was not statistically significant. However, the gains of trade openness on inequality and poverty were reversed when inequality influenced trade openness. In essence, with the influence of inequality, trade openness had an increasing effect on poverty. As a result, this study makes several recommendations to policymakers. To begin, a policy framework must be established to ensure that Nigerian trade is integrated with the rest of the world. Evidence from this study has suggested that policies such as restricting trade through border closures must not feature as a policy option as long as one of the goals of the economy is poverty reduction and reduction in inequality.